PEMBUATAN PANDUAN RANCANGAN PROGRAM PELATIHAN UNTUK MENUNJANG DIMENSI COMPETENCY DEVELOPMENT PADA QUALITY OF WORK LIFE (QWL) DI PT.X - Anindita Chattrawening; Laurentia Verina Halim S.; Eko Nugroho (CALYPTRA, 2018)
Nowadays, especially on bussiness world, training program is an important tools and considered as an investment on organization to support organization objectives. This research is conducted in PT.X, PT. X is one of Indonesia company that run in cement and concrete. Based on pre-assessment and deep interview, PT.X did not know anything about designing a systematic training program. Therefore, this research is to aim designing a training program to guiding and helping PT.X. Researcher, use ADDIE metodology to design a training program in PT.X, because its fit with vision-mision company. The intervention is expected to support competency development dimention on Quality of Work life.